Anxiety Disorders in Pregnancy During The COVID-19 Pandemic: What are The Risk Factors? - Phoebe, Eunike Deborah; Mustikasari, Tiwi; Harmada, Wigaviola Socha Purnama Asri; Octaviana, Dinda Sella; Wolayan, Grahana Ade Chandra; Husnina, Qonita Kanza; Purnomo, Nicholas Fernando; Gotama, Ian Marvin; Tjoewinata, Johan Sebastian; Nyoman Sumiati (Faculty of Medicine, Universitas Airlangga, 2022)
Introduction: The COVID-19 pandemic, since the beginning of 2020, has become a concern for the world community in the health sector. Literature found anxiety symptoms to increase during the COVID-19 pandemic, particularly in the pregnant women population. Objective: This literature review study aims to provide an overview and risk factors for anxiety in pregnancy related to the COVID-19 pandemic. Methods: PubMed and Google Scholar were searched using the following keyword (anxiety disorders) AND (pregnancy) AND (COVID-19) using the journal publication filter for the 2009-2021 issues. Results: Therefore, the psychological condition of pregnant women during COVID-19 pandemic is influenced by various restrictive measures taken by the government and the community, the uncertainty of the pandemic in the future, and most importantly, the fear of being infected so that it can harm the baby they are carrying. Risk factors for anxiety disorders that may be closely related to pregnancy are women who became pregnant for the first time reported having significantly more pregnancy-related anxiety than women who had given birth, high levels of anxiety and depression were found in women with unplanned pregnancies, increased anxiety was associated with worry pregnant women do not receive adequate antenatal care as a result of COVID-19, and a significant correlation was found between higher education and anxiety levels. Conclusion: Risk factors for anxiety disorders in pregnancy are the first pregnancy, unplanned pregnancy, inadequate ANC visits, and higher education. The risk factors that affect pregnant women do not stand alone but simultaneously with each other.